Revision of the genus Theopea Baly (Coleoptera: Chrysomelidae: Galerucinae) of East Asia: species lacking modified clypeus in males and the T. sauteri species group - Lee, Chi-Feng; Bezdĕk, Jan (Zootaxa, 2018)
Theopea Baly, 1864 species lacking a modified clypeus of East Asia are revised. Theopea aureoviridis Chûjô, 1935, T. collaris Kimoto, 1989, and T. sauteri Chûjô, 1935 are redescribed. Theopea coerulea Gressitt & Kimoto, 1963 is removed from synonymy with T. sauteri Chûjô, 1935. Hoplosaenidea irregularis (Takizawa 1978) and H. kanmiyai Kimoto, 1984 are transferred to Theopea and redescribed. A lectotype is designated for T. aureoviridis Chûjô, 1935. Five new species are described, T. cheni sp. nov. from Taiwan, T. geiseri sp. nov. from Northeast India, T. hainanensis sp. nov. from South China (Hainan Island), T. laosensis sp. nov. from West China, North Laos and Vietnam, and T. sekerkai sp. nov. from Central and South Laos.